Factors Affecting Nurse Performance In Outpatient And Emergency Installations Of Inche Abdoel Moeis Hospital, Samarinda - Kadang, Silvia; Ramdan, Iwan Muhammad; Sedionoto, Blego (Mulawarman International Conference on Tropical Public Health, 2025)
Background : In providing good quality and service, it is influenced by the human resources that influence it. Performance is the result of good work in quality and quantity that has been achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. Objective : The purpose of this study was to determine the factors that influence the performance of nurses in the outpatient and emergency installations of the Inche Abdoel Moeis Regional General Hospital, Samarinda City Research Methods/ Implementation Methods : The study design iscross-sectional with a population of nurses in the Outpatient Installation and the Emergency Room at the Inche Abdoel Moeis Hospital. The sample of this research is 57 nurses (total sampling). The instrument used in this research is a questionnaire. Statistical test using chi-square test. Results : The results of the bivariate analysis in this study showed that a relation between motivation and nurse performance (p = 0.043). The work facilities variable also found a relations with the nurse's performance (p = 0.020). The training variable also found a relations with the nurse's performance (p=0.045). The commitment variable also found a relations with the nurse's performance (p=0.001). Conclusion/Lesson Learned : The conclusion of this study is a relations between motivation, work facilities, training and commitment to the performance of nurses in the outpatient and emergency department of the Inche Abdoel Moeis Hospital, Samarinda. Suggestions for the Inche Abdoel Moeis Hospital is continue to improve employee performance, especially in the aspects of motivation, training, work facilities and continue to maintain the commitment of nurses to improve better performance, for further researchers it is possible to do further research with different variables or in different research locations.